Retour à la page blanche après le choc du 11 Septembre - Yves Davo (Sillages Critiques)
In the days that followed the attacks on the World Trade Center on September 11, 2001, a certain number of US cartoonists published their works about the event in a collection untitled 9-11: Emergency Relief. Among these contributions, Jessica Abel’s very short one puzzles the reader in the first place with its powerful “non-picturing”: indeed, whereas the other authors of the collection do their best to picture the attacks in their drawings, she chooses to make the twelve frames of her two plates literally disappear from the page. The author’s view mingles the form with the substance as the unsayable shock emerges at the surface of her comics. The rip within the narrative appears through a gradual yet relentless white shading, and along with this shading goes the obliterating of voices and noises: the page is ultimately returning to pristine white again. Using Abel’s comics, our aim is thus to think over this aesthetics of the void and analyze its particular link with the act of creation. By refusing to represent the event, by erasing the frames themselves, the author questions the role of narration after such a terrorist attempt of erasure, an ethical position which eventually needs to be discussed.